Dust and decay - Maberry, Jonathan (London : Simon & Schuster, 2011)
In post-apocalyptic America, fifteen-year-old Benny Imura and his friends set out into the great Rot & Ruin hoping to find a better future but are soon pitted against zombies, wild animals, insane murderers, and the horrors of Gameland.
Young Adult.
Young Adult
Keywords: Bounty hunters -- Juvenile fiction; Brothers -- Juvenile fiction; Survival -- Juvenile fiction; Zombies -- Juvenile fiction; Bounty hunters -- Fiction; Brothers -- Fiction; Horror stories; Survival -- Fiction; Zombies -- Fiction; Bounty hunters -- Fiction; Brothers -- Fiction; Horror fiction; Survival after airplane accidents, shipwrecks, etc. -- Fiction; Zombies -- Fiction; Horror fiction